KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK PADA MATERI PENYAJIAN DATA MENGGUNAKAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) - Angge Sapto Mubharokh; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Ely Susanti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to determine the students' mathematical reasoning ability in presenting data using Pendidikan Matematika Realistik Indonesia (PMRI). This type of research is descriptive qualitative research. The subjects in this study were 5 students in grade 7. The data collection technique used in the study was a description test which consisted of 5 questions, and interviews. The results obtained after carrying out the research were that there were 2 students who gave rise to all indicators of the student's ability, the other 2 students were quite good at mathematical reasoning abilities. However, the student's mistake was not paying attention or reading the questions carefully and thoroughly. So that the student does not solve the problem in accordance with what was instructed in the question. In addition, there is one student who uses reasoning that focuses on solving problems based on what he observes. These students do not work in accordance with what the questions are instructed to do and do not carry out the mathematical process in working on the questions.